Prognostic potential of neutrophil-to-lymphocyte ratio, platelet to lymphocyte ratio, and monocyte to lymphocyte ratio in acute myocardial infarction patients combined with chronic obstructive pulmonary disease - Dang, Peizhu; Wang, Feiyang; Yu, Hang (Frontiers in Cardiovascular Medicine, 2024)
Background Inflammation is considered to play an important role in chronic obstructive pulmonary disease (COPD) and acute myocardial infarction (AMI), but the relationship between inflammation and poor prognosis in these patients has not yet been studied. Methods We enrolled AMI patients combined with COPD and divided them into three groups according to the tertiles of neutrophil-to-lymphocyte ratio (NLR), platelet to lymphocyte ratio (PLR) and monocyte to lymphocyte ratio (MLR) respectively. Logistic regression analyses were used to identify risk factors for in-hospital all-cause death in these patients. Covariates were adjusted stepwise to determine the association between inflammatory markers and poor prognosis. Also, the receiver operating characteristic (ROC) curve was used to evaluate the greatest predictive indicator for all-cause death. Results A total of 281 AMI patients combined with COPD were enrolled, of which 31 experienced in-hospital mortality. The risk of all-cause death was significantly higher among those with higher NLR. The highest tertile of NLR was significantly associated with an increased risk of all-cause death (all P < 0.05). This association remained significant after adjusting for confounding factors [Odds Ratio (OR): 10.571, 95% confidence interval (CI): 2.307–48.442, P = 0.002]. Moreover, compared to MLR and PLR, NLR had the highest predictive value for all-cause death [area under the curve (AUC): 0.764, 95% CI: 0.681–0.847]. Conclusion In AMI patients combined with COPD, elevated levels of inflammation were associated with increased all-cause mortality. Compared to other inflammatory indicators, NLR may provide a more superior predictive value.